2013
DOI: 10.1513/annalsats.201303-039oc
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Palliative Needs among Older Intensive Care Unit Survivors Transferred to Post–Acute Care Facilities. A Single-Center Study

Abstract: Rationale: Adults with chronic critical illness (tracheostomy after > 10 d of mechanical ventilation) have a high burden of palliative needs, but little is known about the actual use and potential need of palliative care services for the larger population of older intensive care unit (ICU) survivors discharged to post-acute care facilities.Objectives: To determine whether older ICU survivors discharged to post-acute care facilities have potentially unmet palliative care needs. Methods:We examined electronic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
1
22
0
1
Order By: Relevance
“…25 Baldwin and colleagues, in a study of 288 older adult ICU survivors, reported that 88% of patients had at least one palliative care need, while only 6 (2.6%) had received a palliative care consultation while hospitalized. 35 …”
Section: Discussionmentioning
confidence: 99%
“…25 Baldwin and colleagues, in a study of 288 older adult ICU survivors, reported that 88% of patients had at least one palliative care need, while only 6 (2.6%) had received a palliative care consultation while hospitalized. 35 …”
Section: Discussionmentioning
confidence: 99%
“…W jednoośrodko-wej pracy pochodzącej ze Stanów Zjednoczonych podobną śmiertelność (40%) zanotowano dopiero 6 miesięcy po wypisie z oddziału intensywnej terapii. W badaniu tym analizowano jednak chorych powyżej 65 roku życia, a więc znacznie młodszych [15]. Sporą frustrację budzą zresztą także wyniki odległe uzyskane w młodszej grupie wiekowej, w której do miesiąca po wypisie z OAiIT zmarło aż 27,3% chorych, a śmiertelność roczna według analizy Kaplana--Meiera wyniosła 48%.…”
Section: Omó Wi E Ni E W Y Ni K óW I D Ys K U Sj Aunclassified
“…10–12 Consequences of these barriers include emphasis on aggressive rehabilitation through use of the Medicare skilled nursing facility (SNF) benefit and missed opportunities for symptom management. 13–15 …”
Section: Introductionmentioning
confidence: 99%